2004
DOI: 10.1029/2004gl020833
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of two European lakes in response to future climatic changes

Abstract: [1] Temperate deep freshwater lakes are important resources of drinking water and fishing, and regional key recreation areas. Their deep water often hosts highly specialised fauna surviving since glacial times. Theoretical and observational studies suggest a vulnerability of these hydro-ecosystems to reduced mixing and ventilation within the ongoing climatic change. Here we use a numerical thermal lake model, verified over the 20th century, to quantify the transient thermal behaviour of two European lakes in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 28 publications
5
68
1
Order By: Relevance
“…Research using one-dimensional simulation models have predicted periods of stratification in lakes [6]. Research using one-dimensional simulation models have predicted that, in moderate climates, global warming may lead to an oxygen deficit in the deep layers within a half century [7,8]. Previous studies have shown that thermal stability in lakes affects interannual variation of the bottom conditions during winter [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Research using one-dimensional simulation models have predicted periods of stratification in lakes [6]. Research using one-dimensional simulation models have predicted that, in moderate climates, global warming may lead to an oxygen deficit in the deep layers within a half century [7,8]. Previous studies have shown that thermal stability in lakes affects interannual variation of the bottom conditions during winter [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the lengthening of the stratification period and higher stability has been predicted for many lakes (Danis et al, 2004;Fang and Stefan, 2009;Bayer et al, 2013;Gebre et al, 2014;Butcher et al, 2015;Sahoo et al, 2015;etc.). However, the response of stratification patterns to climate shows a higher variability among lakes than the response of surface temperatures (Read et al, 2014).…”
Section: Expected Climate Change Effectmentioning
confidence: 92%
“…But it also means that the renovation time of hypolimnion waters increases greatly with the potential danger of hypoxia. We have not taken into account either the effect of changes in transparency, which can affect the response of lake stratification to climate change (Danis et al, 2004;Butcher et al, 2015). In our case LEC was 0.34 m -1 and since stratification is very sensitive to transparency for low values of the LEC below 0.5 m -1 (Henderson-Sellers, 1988;Heiskanen et al, 2015) potential changes in water transparency could have an important effect on Bimont reservoir hydrodynamics.…”
Section: Effect Of Different Management Optionsmentioning
confidence: 96%
See 2 more Smart Citations